The role of corporate social responsibility (CSR) on women's micro-enterprises: the case of Ezemvelo KZN wildlife - Sosibo, Phumlani Victor (University of the Free State, 2023)
The positive support provided by Ezemvelo KZN Wildlife can potentially transform the entrepreneurial spirit, attitudes, and perceptions among women in rural communities of the KwaZulu-Natal Province. Previous research on women's micro-enterprises has highlighted the importance of empowering women, particularly those living in rural areas such as KwaZulu-Natal. This study specifically focuses on investigating the initiatives of women's micro-enterprises through the corporate social investment programme of Ezemvelo KZN Wildlife. The study was conducted in the Masters Primary Co-operative, using qualitative research methods. A sample of 13 participants involving government officials and co-operative members was selected using purposive sampling. Data was collected through semi-structured interviews and focus group discussions. Thematic analysis was employed to analyse the collected data. The primary objective of this research was to understand how corporate social responsibility contributes to women's micro-enterprise initiatives using Ezemvelo KZN Wildlife as a case study. By focusing on these initiatives, the study aims to shed light on the strategies and practices that lead to the successful and enduring operation of women's micro-enterprises with the organisation's support. Ezemvelo KZN Wildlife’s corporate social development programme has helped to sustain women's micro-enterprises by increasing income generation, business expansion, purchasing necessary equipment, and improving their production capacity, leading to higher revenue and profits. The women also received infrastructural assistance, access to a broader market base, and essential training and capacity building. The study demonstrated that women's micro-enterprises achieve sustainability through teamwork, commitment, and future focus. The study recommends that Ezemvelo KZN Wildlife adopt the Marxist feminist theory approach, the sustainable livelihood approach to corporate social responsibility, and offer continuous training in micro-enterprises to improve their corporate social responsibility programme further.
Dissertation(MDS (Development Studies))--University of the Free State, 2023
Keywords: Ezemvelo KZN Wildlife; Rural communities; KwaZulu-Natal Province; Women's micro-enterprises; Corporate social investment programme; Marxist feminist theory approach; Sustainable livelihood approach